PELATIHAN PENGOLAHAN DATA ADMINISTRASI KEUANGAN MENGGUNAKAN MICROSOFT EXCEL 2013 - Dwi Setyowati; Harmastuti - (DHARMA BAKTI, 2018)
Financial Administration in bookkeeping will make it easier to manage and grow the company. This is due to the large amount of financial data and limited human memory or cannot be maximized. Currently making bookkeeping with the help of MS Excel is quite popular because there are various important tools that serve to complete the financial record. For those working in finance, the most commonly used Excel formulas such as SUMIF, SUMIFS, SUBTOTAL, VLOOKUP, INDEX, and MATCH. Community service activities in the form of training MS Excel 2013, in making financial statements using a combination of Formula IF, OR and SUM Formulas, SUMIF function is used to perform the sum of data with certain criteria and connecting data between sheets. The results achieved by the students of National SMK Nasional Berbah Sleman in this training is able to use and recognize the functions of excel 2013 in processing financial administration data.